2021
DOI: 10.1088/1742-6596/1963/1/012134
|View full text |Cite
|
Sign up to set email alerts
|

Green Syntheses of CdO NPs and evaluation of their antimicrobial activities

Abstract: The aim of this study is to look into the influence of CdO NPs on antimicrobial activity. Green synthesis has been used to produce CdO nanoparticles from cadmium acetate and the Crocus plant in this study. The properties of the synthesized nanoparticles of CdO thin materials were studied (optic, structural, and topographical of surface), it found that the CdO thin film is poly-crystalline and has multiple peaks. The size of crystallite of film calculated by the Scherrer’s formula. The disk method used to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Abdulkareem et.al reported that the CdO NPs modi ed using crocus plant extract with cadmium acetate as a precursor. Obtained NPs inhibit the growth of Staphylococcus aureus and Escherichia coli[29]. Saghatforoush et.al reported that Cd(OH) 2 was prepared by the solvothermal method, using cadmium chloride as source material.…”
mentioning
confidence: 99%
“…Abdulkareem et.al reported that the CdO NPs modi ed using crocus plant extract with cadmium acetate as a precursor. Obtained NPs inhibit the growth of Staphylococcus aureus and Escherichia coli[29]. Saghatforoush et.al reported that Cd(OH) 2 was prepared by the solvothermal method, using cadmium chloride as source material.…”
mentioning
confidence: 99%
“…It dissolves readily in acids but does not dissolve in alkalis. [37][38][39] In this work, we are going to investigate the electronic and optical properties (absorption, reflectivity, and dielectric function) of different zigzag SWCNTs at notations (4, 0), (5, 0) and (6, 0) for undoped and Cd-doped CNTs using the first principal method Cambridge Serial Total Energy Package (CASTEP) code.…”
mentioning
confidence: 99%